Morphology of Lymphoid Tissue in the Lungs of Guinea Pigs Infected with Mycobacterium bovis against the Background of Vaccine Immunity and the Action of Betulin and Its Derivatives - Ivan N. Koshkin; Vasily S. Vlasenko; Valentina I. Pleshakova; Larisa E. Alkhimova; Andrey V. Elyshev; Ivan V. Kulakov (Vaccines, 2022)
Tuberculosis caused by Mycobacterium bovis is a serious problem for animal and human health worldwide. A promising concept for the design of anti-tuberculosis drugs is the conjugation of an immunogenic fraction isolated from bacterial vaccines with a stimulating component. Taking this principle as a basis, conjugates based on BCG antigens with betulin and its derivatives (betulonic and betulinic acids) were designed. The aim of this research was to study the morphological changes in the lymphoid tissue associated with the bronchial mucosa lungs (BALT) in guinea pigs sensitized with experimental conjugates using a model of experimental tuberculosis. The results showed a significant decrease in the BALT response, expressed by a decrease in the diameter of lymphatic follicles and a decrease in their activity when exposed to conjugates based on BCG antigens with betulin and, especially, with betulonic acid, with a visually greater number of plasma cells observed in the lung tissues of guinea pigs of these groups. The absence of tuberculous foci and low BALT activity in the lungs of animals treated with betulin and betulonic acid are probably associated with the activation of humoral immunity under the action of these conjugates.